Prospecting Russula senecis: a delicacy among the tribes of West Bengal - Somanjana Khatua; Arun Kumar Dutta; Krishnendu Acharya (PeerJ, 2015)
Russula senecis, a worldwide distributed mushroom, is exclusively popular among the tribal communities of West Bengal for food purposes. The present study focuses on its reliable taxonomic identification through macro- and micro-morphological features, DNA barcoding, confirmation of its systematic placement by phylogenetic analyses, myco-chemicals and functional activities. For the first time, the complete Internal Transcribed Spacer region of R. senecis has been sequenced and its taxonomic position within subsection Foetentinae under series Ingratae of the subgen. Ingratula is confirmed through phylogenetic analysis. For exploration of its medicinal properties, dried basidiocarps were subjected for preparation of a heat stable phenol rich extract (RusePre) using water and ethanol as solvent system. The antioxidant activity was evaluated through hydroxyl radical scavenging (EC50 5 µg/ml), chelating ability of ferrous ion (EC50 0.158 mg/ml), DPPH radical scavenging (EC50 1.34 mg/ml), reducing power (EC50 2.495 mg/ml) and total antioxidant activity methods (13.44 µg ascorbic acid equivalent/mg of extract). RusePre exhibited antimicrobial potentiality against Listeria monocytogenes, Bacillus subtilis, Pseudomonas aeruginosa and Staphylococcus aureus. Furthermore, different parameters were tested to investigate its chemical composition, which revealed the presence of appreciable quantity of phenolic compounds, along with carotenoids and ascorbic acid. HPLC-UV fingerprint indicated the probable existence of at least 13 phenolics, of which 10 were identified (pyrogallol > kaempferol > quercetin > chlorogenic acid > ferulic acid, cinnamic acid > vanillic acid > salicylic acid > p-coumaric acid > gallic acid). Result from the present work suggests that the fraction, RusePre, may open novel prospect as a functional ingredient in antioxidant supplements and in drugs to treat infectious disease.